Learning Integration of Islamic Education for ex-prison Children at SMK Istimewa Tangerang Banten - Ginanjar, Muhammad Hidayat (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
The phenomenon of adolescents that cause crime is quite alarming in a child's social environment. Vocational High School (SMK) Istimewa Tangerang is part of the education at the Institute for Child Special Development (LPKA). This study aims to describe the learning model of the integration of Islamic Education (PAI) for students of Vocational High School in Tangerang. The method used is qualitative with descriptive analysis. The results showed that the learning model integrating Islamic Education (PAI) improved moral morals and personality effectively. Appropriate learning methods become the main instrument in the development of the PAI integration learning model. Moral changes in moral attitudes are the leading indicators of Learning Success Attitudes. In the future, the need for developing learning integration models is in line with the development of pesantren. The pesantren model is a participant for participants.